International Monetary Fund Annual Report 1972. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1972)
This paper reviews key findings of the IMF's Annual Report for the fiscal year ended April 30, 1972. The report highlights that the main features of world economic developments in 1971 were a continuation of slow output growth coupled with inflation and the succession of currency crises, involving capital movements and foreign exchange reserve increases of unprecedented magnitude that led to the December 18 realignment of major currencies. During the first half of 1972, the picture with respect to certain aspects of these problems improved significantly.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet